2005
DOI: 10.1007/s00299-005-0932-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficient plant regeneration protocol through callus for Saussurea obvallata (DC.) Edgew. (Asteraceae): effect of explant type, age and plant growth regulators

Abstract: A callus induction and in vitro plantlet regeneration system for the endangered state flower of Uttaranchal (Saussurea obvallata) was optimized by studying the influence of explant type (root, hypocotyl, cotyledon and leaf), age and different concentrations of plant growth regulators. Explants from 10 to 15-day-old seedlings showed maximum callus induction. Callus formation and shoot differentiation was initiated on Murashige-Skoog (MS) medium containing 6-benzyladenine (BA) and alpha-naphthalene acetic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
50
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 18 publications
7
50
1
Order By: Relevance
“…In the present study, leaf is a better explant source for the species with its 100% of callus induced in MS medium supplemented with BA and NAA. This result was fairly consistent with other species tested [28,33,37]. The intercalary meristems distributed in leaves might be responsible for the higher regeneration potential.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the present study, leaf is a better explant source for the species with its 100% of callus induced in MS medium supplemented with BA and NAA. This result was fairly consistent with other species tested [28,33,37]. The intercalary meristems distributed in leaves might be responsible for the higher regeneration potential.…”
Section: Discussionsupporting
confidence: 81%
“…Previous reports showed that PGR requirements for callus induction vary depending on the explants types in Asteraceae species [33][34][35], and such variations can be attributed to the physiological condition of the explant, which is determined by genetic factors [36]. In the present study, leaf is a better explant source for the species with its 100% of callus induced in MS medium supplemented with BA and NAA.…”
Section: Discussionmentioning
confidence: 66%
“…Acacia sinuata (Vengadesan et al 2002) and Tamarindus indica (Muhammad and Amusa 2003). The explant dependent callus proliferation and inter-explant variability is a common phenomenon usually observed during the callus induction in some systems (Arockiasamy and Ignacimuthu 1998;Pereira et al 2000;Dhar and Joshi 2005;Thomas and Maseena 2006). Regardless of cytokinin type and concentration, the amount of callus produced increased significantly when 0.5 mgl −1 NAA was incorporated in the medium.…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of the culture media and cultivar, leaf tissues gave the best yield of callusing. Leaves are known to be most totipotent, capable of becoming de-differentiated tissues (Dhar and Joshi, 2005). In Zinnia cell cultures, a perfect model for cell wall synthesis and programmed cell death in plants, mesophyll cells of young leaves are known to be highly totipotent.…”
Section: Discussionmentioning
confidence: 99%